Molecular Characterization of MbraOR16, a Candidate Sex Pheromone Receptor in Mamestra brassicae (Lepidoptera: Noctuidae). Issue 5 (24th September 2018) - Köblös, Gabriella; François, Marie-Christine; Monsempes, Christelle; Montagné, Nicolas; Fónagy, Adrien; Jacquin-Joly, Emmanuelle
Abstract: Sex pheromone communication in Lepidoptera has long been a valuable model system for studying fundamental aspects of olfaction and its study has led to the establishment of environmental-friendly pest control strategies. The cabbage moth, Mamestra brassicae (Linnaeus) (Lepidoptera: Noctuidae), is a major pest of Cruciferous vegetables in Europe and Asia. Its sex pheromone has been characterized and is currently used as a lure to trap males; however, nothing is known about the molecular mechanisms of sex pheromone reception in male antennae. Using homology cloning and rapid amplification of cDNA ends-PCR strategies, we identified the first candidate pheromone receptor in this species. The transcript was specifically expressed in the antennae with a strong male bias. In situ hybridization experiments within the antennae revealed that the receptor-expressing cells were closely associated with the olfactory structures, especially the long trichoid sensilla known to be pheromone-sensitive. The deduced protein is predicted to adopt a seven-transmembrane structure, a hallmark of insect odorant receptors, and phylogenetically clustered in a clade that grouped a majority of the Lepidoptera pheromone receptors characterized to date. Taken together, our data support identification of a candidate pheromone receptor and provides a basis for better understanding how this species detects a signal critical for reproduction.